Penentuan Tingkat Buta Warna Pada Citra Ishihara Berbasis HSV Dan Algoritma Color Filtering - Alfian Syaifudin; Yustina Retno WU; Teguh Susyanto (Jurnal Ilmiah SINUS, 2020)
Currently, the use of computer media for measuring the level of color blindness for the recruitment of prospective workers in companies/organizations or the selection of prospective students in educational institutions is still rare. Most methods used to measure the level of color blindness still use conventional methods without involving a lot of computer media. The reason is that the level of color blindness measuring devices is still not affordable for companies or educational institutions. Based on this fact, a proposed method for measuring color blindness using computer media is by applying the Color Filtering algorithm to the HSV color space on the Ishihara images. The purpose of this paper is to design and build applications to detect the level of color blindness using the Color Filtering algorithm. The color filtering algorithm is an image processing technique that is used to manipulate an image based on the specific color obtained from a color space. The use of HSV color space is used because the human eye uses Hue to refer to colors known to humans, such as red and green. This property reflects the colors captured by the human eye that respond to various wavelength values of light. The results of this paper are the application of the Color Filtering algorithm to Ishihara-based HSV images expressed as highly relevant for detecting the level of a person's color blindness.